White Matter Abnormalities in Schizophrenia and Schizotypal Personality Disorder. (23rd June 2014) - Lener, Marc S.; Wong, Edmund; Tang, Cheuk Y.; Byne, William; Goldstein, Kim E.; Blair, Nicholas J.; Haznedar, M. Mehmet; New, Antonia S.; Chemerinski, Eran; Chu, King-Wai; Rimsky, Liza S.; Siever, Larry J.; et al.
Abstract : Prior diffusion tensor imaging (DTI) studies examining schizotypal personality disorder (SPD) and schizophrenia, separately have shown that compared with healthy controls (HCs), patients show frontotemporal white matter (WM) abnormalities. This is the first DTI study to directly compare WM tract coherence with tractography and fractional anisotropy (FA) across the schizophrenia spectrum in a large sample of demographically matched HCs ( n = 55), medication-naive SPD patients ( n = 49), and unmedicated/never-medicated schizophrenia patients ( n = 22) to determine whether (a) frontal-striatal-temporal WM tract abnormalities in schizophrenia are similar to, or distinct from those observed in SPD; and (b) WM tract abnormalities are associated with clinical symptom severity indicating a common underlying pathology across the spectrum. Compared with both the HC and SPD groups, schizophrenia patients showed WM abnormalities, as indexed by lower FA in the temporal lobe (inferior longitudinal fasciculus) and cingulum regions. SPD patients showed lower FA in the corpus callosum genu compared with the HC group, but this regional abnormality was more widespread in schizophrenia patients. Across the schizophrenia spectrum, greater WM disruptions were associated with greater symptom severity. Overall, frontal-striatal-temporal WM dysconnectivity is attenuated in SPD compared with schizophrenia patients and may mitigate the emergence of psychosis.